Understanding and teaching the Holocaust - Hilton, Laura June, 1969-; Patt, Avinoam J. (Harvey Goldberg series for understanding and teaching history., 2020)
"Few topics in modern history draw the attention that the Holocaust does. The Shoah has become synonymous with unspeakable atrocity and unbearable suffering. Yet it has also been used to teach tolerance, empathy, resistance, and hope. Understanding and Teaching the Holocaust provides a starting point for teachers in many disciplines to illuminate this crucial event in world history for students. Using a vast array of source materials--from literature and film to survivor testimonies and interviews--the contributors demonstrate how to guide students through these sensitive and painful subjects within their specific historical and social contexts. Each chapter provides pedagogical case studies for teaching content such as antisemitism, resistance and rescue, and the postwar lives of displaced persons. It will transform how students learn about the Holocaust and the circumstances surrounding it."